The Impact of the Effectiveness of Tourism Media on Domestic Tourism (Czech Journal of Multidisciplinary Innovations, 2023)
The research was under the title (Effectiveness of Tourism Media in Domestic Tourism), and the research study consisted of four main topics. The theory of the analytical method in interpreting and understanding the results of the questionnaire; and field method, Where the focus was on the field study within a random sample of society of different groups, ages, races and scientific levels to express their opinions in the context of the same topics. And the requirements for the success of tourism media. As for the third topic, it contained the introduction, the concept of tourism, the types and forms of tourism, the advantages and dimensions of internal tourism, as well as the characteristics of internal tourism. Finally, the fourth topic, which is the field and applied research, and included analysis tables, questionnaire form, results and recommendations.